Human Resource Management: (Studi Kasus Pembangunan Proyek Gowa Discovery Park) - Retno Angraeni S; Irianti Irianti; Syarifuddin Syarifuddin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to find out how the agreement process occurred between PT Mira Megah Wisata, the Government, and the community in resolving conflicts of interest during the construction process of the Gowa Discovery Park project. This research used a qualitative with a case study approach, the interview process was carried out in an unstructured interview where the determination of informants was carried out by snowball sampling technique, the first selected informant directed the researcher to meet other people who had the potential to answer research questions. The results of the study were then processed using the triangulation technique of data reduction, presentation, and conclusion drawing. The results showed that the investors utilized a human resource management strategy where they recruited people who opposed the development to work in the GDP tourism arena, this process consisted of selection, performance assessment, rewards, and development. This human resource management proved to be a win-win solution where a balanced function of control and commitment was built where the community and investors became aligned in understanding each other's needs and desires.